2020
DOI: 10.1101/2020.11.09.20228221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The metabolic fingerprint of COVID-19 severity

Abstract: Corona virus disease 2019 (COVID-19) has been associated with a wide range of divergent pathologies, and risk of severe disease is reported to be increased by a similarly broad range of co-morbidities. The present study investigated blood metabolites in order to elucidate how infection with severe acute respiratory syndrome coronavirus 2 can lead to such a variety of pathologies and what common ground they share. COVID-19 patient blood samples were taken at hospital admission in two Belgian patient cohorts, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 58 publications
5
23
0
Order By: Relevance
“…[39] Cholesterol has been proposed to promote SARS-CoV-2 infection by multiple mechanisms, including promoting ACE2 and furin trafficking to viral entry points, [34] but plasma levels are reduced in patients with established disease and correlate inversely with disease severity. [16,27,40,41] When considered together with previous findings of cholesterol binding to the spike protein, our results…”
Section: Research Articlessupporting
confidence: 83%
See 1 more Smart Citation
“…[39] Cholesterol has been proposed to promote SARS-CoV-2 infection by multiple mechanisms, including promoting ACE2 and furin trafficking to viral entry points, [34] but plasma levels are reduced in patients with established disease and correlate inversely with disease severity. [16,27,40,41] When considered together with previous findings of cholesterol binding to the spike protein, our results…”
Section: Research Articlessupporting
confidence: 83%
“…[12] Also we note that arecent study seeking biomarkers for COVID-19 found that disease severity was associated with lower circulating levels of polyunsaturated fatty acids,such as linoleic acid. [16] Va rious drug targeting strategies,i ncluding extensive computational efforts,s ometimes as part of extensive,o pen science collaborative programs (e.g.t he COVID Moonshot project) have been employed to design both competitive and covalent inhibitors for the SARS-CoV-2 targets,n otably the main protease. [17] While there have been intensive efforts to target several SARS-CoV-2 proteins, [18][19][20][21] efforts to modulate the function of the spike protein are to our knowledge more limited, although covalent stabilisation of the closed form of the spike for example,byintroduction of disulphide bonds [22] is relevant for vaccine development as well as,p otentially, small molecule therapeutic development.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies identified that LA binds to a fatty acid binding pocket in the SARS-CoV-2 spike protein stabilizing its confirmation in a manner that decreases viral entry into the host cell ( Toelzer et al, 2020 ). In support of this finding, Dierckx et al (2020) demonstrated high LA concentrations associated with lower COVID-19 severity. Neither study monitored LA metabolites therefore making it impossible to understand the biological roles of the metabolites and how they may impact interpretation from other studies.…”
Section: Discussionsupporting
confidence: 67%
“…Of note, the levels of many of the mentioned metabolites in severe COVID-19 (WHO score 4-7) were higher by more than three standard deviations than the mean of a large non-COVID population from the UK Biobank (150,000 samples) 42,43 , illustrating the degree of metabolic disarray in the serum of COVID-19 patients with severe disease. These results are also in agreement with previous reports 24,44 .…”
Section: Resultssupporting
confidence: 94%
“…One possible approach is to increase the dimensionality of the system by the use of mixed-modality profiling such as the combination of immune population quantification and circulating cytokine levels 22,23 . While much work has been done on the characterization of the host immune response through cytometric or serological methods, characterization of the metabolic state of COVID-19 patients has just begun [24][25][26] . There are several lines of evidence demonstrating the importance of metabolic species -in particular lipids -during viral infection.…”
Section: Introductionmentioning
confidence: 99%